Exploration of Islamic Values in Fisherman Settlements Mandar Lero Tribe - Muhammadiah, Muhammad Jabir; Asmal, Idawarni; Syarif, Edward (PT. Riset Press International, 2023)
It is contained in the Al-Qur'an and Hadith, Islamic values are moral teachings that are abstract and concrete, namely verbal and nonverbal. This can be expressed in settlements and dwellings both non-physically and physically. This can be seen in the fishing settlements of the Mandar Lero tribe which are influenced by the real nature of Islam and the interrelationships of the five components of settlement development: nature, humans, society, physical and network. This research is expected to be able to distinguish and determine the significance of Islamic characteristics related to the five components of settlement development in fishing settlements of the Mandar Lero tribe, Suppa Region, and Pinrang Regency. This exploration is directed by using subjective graphic examination techniques, gathering information through top-down meetings with informants and perceptions, then the results are dissected into two fundamental components, namely the characteristics of Islam and its relation to the five components of physical settlement development and non-physical parts. The consequence of the review shows that the relationship between the quality of Islam and the five components of settlement arrangement is closely related to tidiness, utilization of nearby materials, family and individual firmness, friendly constancy and “sayyang pattud'du” (horse dancing) parties, presence of mosques, schools and offices. in settlements, utility networks. This exploration can be used as a perspective in managing and building settlements and houses with an Islamic perspective.